A Study on the Development of Baju Kurung Design in the Context of Cultural Changes in Modern Malaysia - Hanisa Hassan (Wacana Seni Journal of Arts Discourse, 2016)
The baju kurung is a type of traditional dress used by Malay descendants in the Nusantara. The baju kurung is prevalent in countries such as Malaysia and Indonesia (Jambi, Riau, Padang, Bentan). Although these countries might refer to the style using different names, the baju kurung is defined by its similar cut and pattern. The advancement of current fashion has changed the concept and understanding of the baju kurung, which is closely related to changes in Malay cultural phenomena. This study examines modifications to baju kurung designs to determine if the style still represents the identity of Malay women. This study takes a qualitative approach by applying the aesthetic morphology analysis method to understand how design developments correspond to the cultural changes in modern Malaysia. This study focuses on the current development of baju kurung designs by using several samples of baju kurung designs by local Malay designers as the primary data. Historical references of baju kurung are used to identify variables that may have changed in modern designs. The findings indicate that the development of modern baju kurung corresponds to a cultural development process that has slightly altered the visual identity of Malay women living in Malaysia.